The role of AI on the entrepreneurial and innovative mindset of university students in MENA and Canada and the overall impact on the student’s readiness: A comparative study - Moustafa, Ayman; Rabie, Nada; Mejri, Sami; Alshehhi , Mozah (Journal of International Students, 2026)
Since the beginning of 2023, we have been exposed extensively to a new feature of Revolution 4.0 called artificial intelligence (AI). Recently, AI has been extensively implemented in different sectors and industries. Accordingly, AI has become a core component of different business processes and sectors. Among these sectors in which AI is disrupted are the entrepreneurship and education sectors. This study investigates how university students in the United Arab Emirates (UAE) and Canada view innovation and entrepreneurship in relation to AI. AI has the potential to revolutionize how students approach innovation, creativity, and opportunity recognition as it becomes more integrated into business processes, education, and entrepreneurship. Through the application of a cross-sectional comparative quantitative methodology, the study evaluates how AI improves students’ ideation, prototyping, and market analysis skills, thereby increasing their preparedness for the workforce. Surveys were used at universities in both regions to gather data, with an emphasis on the opinions and experiences of students using AI-driven tools. This study contributes to the continuing academic conversation on the role of AI in forming future entrepreneurs by offering insights into regional variations in AI adoption and its implications for educational programs.